Perception of physicians from a Medical school in Lima on training in medical procedures during internship - Taype Rondán, Álvaro (2016)
Objectives. To evaluate the perception of recently graduated physicians on their training in medical procedures during internship, and to determine factors associated to adequate training in a greater number of procedures at a university in Lima, Peru. Design. Observational, cross-sectional, analytical study. Setting. Universidad de San Martín de Porres, Lima, Peru. Participants. Recently graduated physicians. Methods. Survey study in medical graduates from a private university in Lima, Peru, who finished medical internship in 2014. Facebook social network was used to locate participants. Informed consent was obtained and a self-report survey was sent to collect sociodemographic characteristics and perceptions on their medical internship. Main outcome measures. Perception on medical procedures training during internship. Results. One hundred seventeen surveys were analyzed. The number of hours worked per day was on average 10.0 ± 1.8, the frequency of excessive workload and "excessive paperwork" in at least one rotation was respectively 80.3% and 84.6%. Few respondents received adequate training during their internship in the administration of injections (53.9%), reduction of fractures (28.2%), and vertical vaginal deliveries (27.4%). Having adequate training in more than 20 procedures was associated to having an adequate teaching in three or four rotations (PR = 2.55, 95% CI = 1.36 to 4.76), and to work on average 9 hours 30 minutes to 10 hours 15 minutes daily compared with less working hours per day (PR = 1.91, 95% CI = 1.01 to 3.64). Conclusions. Excessive workload and paperwork as well as reduced working hours seem to affect negatively the number of medical procedures in which the interns feel adequately trained. It is necessary to implement strategies to improve teaching at boarding school.